Influence of maternal obesity on the skeletal muscle of offspring - Ana L. Álvarez-Chávez; Patricia Canto (Permanyer, 2022)
Maternal obesity has been described as a clinical entity associated with an increased incidence of metabolic diseases in the offspring, indicating a fetal programming phenomenon during this critical development period. Fetal exposure to an obesogenic environment affects multiple organs and tissues, including skeletal muscle, which is particularly susceptible to stressors from the external environment. Several studies have described alterations in the morphology and composition of skeletal muscle tissue secondary to obesogenic exposure in utero. In addition, modifications in signaling pathways related to the metabolism of energy substrates have been found in children born to mothers with obesity during pregnancy. This review addresses the current evidence describing the consequences of fetal exposure to an obesogenic maternal diet on skeletal muscle tissue, focusing on changes in tissue composition, alterations in signaling pathways related to glucose and fatty acid metabolism, mitochondrial biogenesis, and oxidative phosphorylation.